Safety and Tolerability of Mosquito Bite-Induced Controlled Human Infection with Plasmodium vivax in Malaria-Naive Study Participants—Clinical Profile and Utility of Molecular Diagnostic Methods. (23rd June 2021) - Kamau, Edwin; Bennett, Jason W; Yadava, Anjali
Abstract: Background: Plasmodium vivax controlled human malaria infection ( Pv CHMI) is an important tool for evaluation of drugs, vaccines, and pathologies associated with this parasite. However, there are few data on safety due to limited numbers of Pv CHMIs performed. Methods: We report clinical and laboratory data, including hematological and biochemical profiles and adverse events (AEs), following mosquito bite-induced Pv CHMI in malaria-naive study participants. Malaria diagnosis and treatment initiation was based on microscopic analysis of Giemsa-stained slides. Exploratory molecular assays were used to detect parasites using real-time polymerase chain reaction (PCR). Results: AEs were mild to moderate and no study-related severe AEs were observed in any study participants. The majority of symptoms were transient, resolving within 48 hours. Molecular diagnostic methods detected parasitemia in 100% of study participants before malaria diagnosis using microscopy. Of reported AEs, microscopy detected 67%–100%, quantitative PCR 79%–100%, and quantitative real-time reverse-transcription PCR 96%–100% of study participants prior to appearance of symptoms. Almost all symptoms appeared after initiation of treatment, likely as known consequence of drug treatment. Conclusions: Pv CHMI is safe with the majority of infections being detected prior to appearance of clinical symptoms, which can be further alleviated by using sensitive molecular methods for clinical diagnosis. Clinical Trials Registration . NCT01157897. Abstract : Mosquito bite-induced P. vivax controlled human malaria infection results in moderate or mild clinical symptoms and transient deviations in biochemical and hematological parameters. Utilizing molecular diagnostic methods alleviates these further, making this a safe model to evaluate biology and interventions.